A modular mechatronic gripper installed on the industrial robot KUKA KR 60-3 for boxing, unpacking and selecting of beverage bottles - Andrade, Ronald Gerson Villanueva (2022)
Nowadays, bottling industries perform inefficient maintenance and transportation sub-processes, such as: boxing, unpacking, and selecting. These functions are performed by workers during long hours, which causes delays in the general production process, risks in the safety of personnel and integrity of the bottles, a tendency to a greater number of errors and especially, severe medical problems caused in the long term. In view of the advantages of industrial automation, it is known that it makes use of the union of engineering knowledge to facilitate procedures and guarantee reliability. This is the case of industrial robots that are increasingly required to optimize numerous systematic strategies in many fields; however, it is complex to develop an autonomous artifact that adapts to variable changes in different environments. Despite the existence of interesting projects for grippers or claws to lift objects, several of them lack adaptability regarding the type of element they handle and among other deficiencies. For these needs, a Modular Mechatronic Gripper was designed and installed on the Industrial Robot KUKA KR 60-3; having characteristics of versatility and dynamism to load and unload 12 glass or plastic bottles, personal or medium size; and all of them at the same time efficiently and safely. Likewise, the automatic machine can be used with different box layouts or different industrial robots, by means of simple component modifications. With the dexterity of the mechatronic system, the time required for the aforementioned sub-processes was reduced by 72% and it is expected to improve the health of the employees.